2010
DOI: 10.1111/j.1751-1097.2010.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Low‐level Light Therapy Increases Cytochrome Oxidase in Skeletal Muscle

Abstract: Low-level light therapy (LLLT) increases survival of cultured cells, improves behavioral recovery from neurodegeneration and speeds wound healing. These beneficial effects are thought to be mediated by upregulation of mitochondrial proteins, especially the respiratory enzyme cytochrome oxidase. However, the effects of in vivo LLLT on cytochrome oxidase in intact skeletal muscle have not been previously investigated. We used a sensitive method for enzyme histochemistry of cytochrome oxidase to examine the rat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 63 publications
2
53
0
3
Order By: Relevance
“…Hayworth et al [12] reported modulations in Cox activity 24 h after the use of light therapy on the temporalis muscles in rats, but these modulations were dependent on the type of metabolism in muscle fibers that in turn suggested differences in energy synthesis (ATP). For this reason, our study assessed the effect of LEDT on ATP synthesis in muscles with either a predominance of aerobic metabolism (soleus) and mixed aerobic and glycolytic metabolism (gastrocnemius) [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hayworth et al [12] reported modulations in Cox activity 24 h after the use of light therapy on the temporalis muscles in rats, but these modulations were dependent on the type of metabolism in muscle fibers that in turn suggested differences in energy synthesis (ATP). For this reason, our study assessed the effect of LEDT on ATP synthesis in muscles with either a predominance of aerobic metabolism (soleus) and mixed aerobic and glycolytic metabolism (gastrocnemius) [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that taking advantage of the double absorption bands (red and near-infrared together) could optimize the effects of photobiomodulation to promote ATP synthesis and fatigue-muscle resistance. Moreover, light therapy was delivered without contact as reported previously [12,24], covering all target muscles (gastrocnemius, soleus, gluteus, and lower back muscles) and made it possible to stimulate entire muscle groups simultaneously as reported previously [31]. Finally, as the light irradiation was performed without contact, possibly reflection of the light on the animal surface (mainly on the curved areas) would have occurred in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LLLT has been found to accelerate wound healing and reduce pain, possibly by stimulating oxidative phosphorylation and reducing inflammatory responses, thus producing several beneficial effects upon inflammation and healing [10][11][12][13][14][15][16][17]. In skeletal muscle, LLLT has been effective at promoting improvements in electrical activity, preventing fatigue induced by tetanic contractions and improving healing after traumatic injury [11]. At the molecular level, LLLT directly stimulates the activity of cytochrome oxidase in muscle fibers, triggering a series of biochemical cascades that improve cellular functions [12].…”
Section: Introductionmentioning
confidence: 99%
“…13 Following the application of photobiostimulation of tissues, a selective stimulation of mitochondrial activity is seen to occur, providing more elevated levels of cellular respiration as well as the synthesis of ATP, which results in the acceleration of mitosis. 14,15 An energy density of 5J/cm 2 was chosen for the application at each point where there was the greatest muscle contraction reaction (deep muscle fibers) to palpation of the muscles selected for this report.…”
mentioning
confidence: 99%